The Effect Of Net Working Capital On The Company’s Market Value - Ghanem Wadi, Amir; Qassem Sobeih, Firas (Iraqi Journal for Administrative Sciences, 2024)
The main purpose of this study is to show the extent of the influence of the independent variable, net working capital, on the dependent variable, the market value in some of the (6) industrial companies registered in the Iraq Stock Exchange, where the necessary information was obtained through the financial reports of the Iraq Stock Exchange. For the period from 2011-2019, as the study relied on a number of statistical tools and methods such as simple linear regression analysis as well as the financial analysis of the study’s indicators (net working capital, market value) and in light of the results, which were reached, there is an impact relationship for the net index The working capital depends on the market value of the company (plastic, sewing, Al-Mansour, carpets) and one of the most important recommendations is to pay attention to maintaining the working capital in a balanced manner while taking advantage of investment opportunities in a way that leads to the ability of companies to meet their obligations and at the same time the optimal investment for those funds.